Population Genetics of Tor douronensis in Sarawak - Muhammad Amirul Arib, bin Md Adzhar (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Tor douronensis, known locally as Semah, is one of the valuable and potential resources in Sarawak due to its high food value and demand as game fish. Several molecular studies related to T. douronensis had been carried out but limited in populations. No study had involved T. douronensis from Bakun. Therefore, this study was designed to infer population subdivision, the genetic structure, evolutionary neutrality, and population expansion of T. douronensis among 4 populations from Sarawak including Bakun using partial DNA sequencing of the Cytochrome c oxidase I (COI) mtDNA gene. A total 465 bp of CO1 gene of T. douronensis had been successfully amplified, and based on phylogenetic tree, there are 3 distinct geographical population subdivision observed (Central, Southern, and Northern population); 1st clade (haplogroup I) from Bakun, 2nd clade (haplogroup II) from Layar and 3rd clade (haplogroup III) from Ba Kelalan and Ulu Limbang. Overall, there were 13 haplotypes and none is shared by any population. Low level gene flow has been observed. Small number of migrants per generation (Nm<1.0) among the population indicated the small population or separated populations with large geographical and topological barrier. Population expansion was undergone for the species for the whole populations except for northern population as shown by small and non-significant values of the sum of the standard deviation of the observed (SSD<0.5) and expected mismatch distributions (unimodal) and Harpending raggedness index (r <1.2). Furthermore a large negative value and significant test of Fu’ Fs in Bakun population suggested recent expansion. The result also suggested that all the populations do not deviate with evolutionary neutrality supported with no significant in Tajima’s neutrality test (p<0.05).